2013
DOI: 10.15191/nwajom.2013.0114
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of lake-effect snowstorms in western New York

Abstract: The Great Lakes region of the United States is subjected to a wintertime convective phenomenon known as lake-effect snow (LES). These events are capable of producing significant quantities of snow over localized areas by developing elongated bands that tap into heat and moisture exchanges between the warm lake surface and the overlying continental polar air. Several factors are believed to affect the snowfall intensity associated with LES events, including the ice coverage over the lake where the snowbands ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Additionally, the warmer (cooler) lake surfaces during winter/nighttime (summer/daytime) tend to generate a convergent (divergent) flow due to the lake-land thermal gradient, which enhances (suppress) the over-lake convective development and cloud formation (Ruthrich et al 2015;Zhao et al 2012). Such lake effects can lead to increases of precipitation and heavy snowfall during winter especially in the downwind regions (Pereira and Muscato 2013;Theeuwes et al 2010;Vavrus et al 2013). Different from the climatic effect of the Great Lakes, Samuelsson et al (2010) found that the lakes in the northern Europe with temperate climate act to increase T 2m for all seasons and enhance the convective precipitation during late summer and early autumn.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the warmer (cooler) lake surfaces during winter/nighttime (summer/daytime) tend to generate a convergent (divergent) flow due to the lake-land thermal gradient, which enhances (suppress) the over-lake convective development and cloud formation (Ruthrich et al 2015;Zhao et al 2012). Such lake effects can lead to increases of precipitation and heavy snowfall during winter especially in the downwind regions (Pereira and Muscato 2013;Theeuwes et al 2010;Vavrus et al 2013). Different from the climatic effect of the Great Lakes, Samuelsson et al (2010) found that the lakes in the northern Europe with temperate climate act to increase T 2m for all seasons and enhance the convective precipitation during late summer and early autumn.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a lake, due to its unique physical properties and sharp contrast with surrounding land areas, usually exerts a significant influence on local weather and climate [ Jacobs and Grondin , ; Bates et al ., ; Scott and Huff , ; Schmidlin , ; Long et al ., ; Rice , ]. Owing to its severe negative impacts such as economic losses and severe casualties, lake‐effect snowstorms, which occur over northern and temperate lake areas during cool seasons when the relatively warm water heats and moistens the overlying cold air mass that passes over the lakes and thus leads to an enhancement of precipitation in the downwind regions, have been primarily documented [ Lavoie , ; Niziol et al ., ; Notaro et al ., ; Pereira and Muscato , ; Ulrich and Janiszeski , ]. Moreover, selection of study regions has mainly focused on large and deep lakes, such as the Great Lakes [ Lavoie , ; Hjelmfelt , ; Notaro et al ., ; Vavrus et al ., ], the Great Salt Lake [ McMillen and Steenburgh , ], and the Lake Victoria Basin [ Song et al ., ; Sun et al ., ; Williams et al ., ].…”
Section: Introductionmentioning
confidence: 99%